Specification for nickel-chromium-cobalt-titanium-aluminium heat-resisting alloy wire for thread inserts (0.45 mm to 2 mm diameter) (nickel base, Cr 19.5, Co 18.0, Ti 2.5, Al 1.5). (12th February 1973) - British Standards Institution,
No abstract available